Promoting Active Commuting to School Through Environmental and Policy Supports in Buffalo, New York. (May 2015) - Raja, Samina; Booth, Justin; Norton, J. Travis; Crowell, Beverly; Gouck, Jessie; Bonaro, Kari
Abstract : Background: Children in Buffalo, New York, have limited opportunities for safe, enjoyable physical activity. The Healthy Kids, Healthy Communities–Buffalo partnership established in 2009 created environmental and policy supports to facilitate physical activity among youth. Methods: This article uses a mixed-methods approach to document environment and policy changes in support of active commuting to school. Built environment data were collected using a pre-post research design with the Street Design Environmental Audit Tool. Supplementary sources of information include Geographic Information Systems, US Census data, and property parcel data. Results: This exploratory study found modest improvements in the built environment during the period of assessment. Specifically, sidewalk conditions were improved. In addition, assessment of citywide policy indicates that systemic supports for active living have been put into place through the new (proposed) land use plan and the proposed zoning ordinance. Conclusions: Exploratory evaluation results suggest that Healthy Kids, Healthy Communities–Buffalo partnership was able to make some environmental and policy changes to promote active transportation. A long-term assessment is required to develop a fuller understanding of how environmental and policy changes impact active transportation. Abstract : This article uses a mixed-methods approach to document environment and policy changes in support of active commuting to school in Buffalo, New York.